The Principle of Freedom of Contract In Practice: Between The Theory and Reality of Economic Inequality in Indonesia - Makaarim, Arvhia Marella; Sabrina, Almas; Farhan, Reza (Advances In Social Humanities Research, 2025)
The principle of freedom of contract, rooted in classical individualism and adopted into the Indonesian legal system via Dutch civil law, grants parties the liberty to create agreements based on mutual consent. While this principle remains fundamental in Indonesian contract law—as enshrined in Article 1338 of the Civil Code—it is not absolute. In practice, especially within business relationships involving micro, small, and medium enterprises (MSMEs) and large corporations, significant disparities in bargaining power challenge the ideal of contractual equality. Empirical findings indicate that MSMEs often face one-sided contract terms due to their weaker economic position, lack of legal resources, and limited access to capital. This study aims to critically examine the implementation of the principle of freedom of contract in Indonesia, particularly regarding its impact on MSMEs. Using a juridical-normative method and a legislative approach, combined with case study analysis, the research explores the gap between legal theory and economic reality. The findings reveal that while the freedom of contract remains theoretically intact, its execution frequently undermines the position of weaker parties. The study suggests reconstructing the application of this principle within the framework of social justice, recommending enhanced regulation of standard contracts, fair contract guidelines, and an active role for the state in protecting MSMEs. These efforts are essential to ensure that contractual freedom functions not only as a legal doctrine but as a tool for equitable and inclusive economic participation.